2005
DOI: 10.1007/s00056-005-0515-3
|View full text |Cite
|
Sign up to set email alerts
|

Determining Skeletal Parameters in Angle Classes II, Division 1 and II, Division 2*

Abstract: Significant differences existed in skeletal morphology between patients with Angle Class II, Division 1 and II, Division 2, with only minor gender-specific differences: angleML/NSL in Class II, Division 2 males (p < 0.01) and females (p < 0.05) was smaller compared to Class II, Division 1 patients. angleML/NL was also noticeably smaller in Class II, Division 2 males (p < 0.001) and females (p < 0.01) compared to Class II, Division 1 patients. Patients with Class II, Division 2 had a smaller gonial angle (angle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 41 publications
(87 reference statements)
3
7
0
Order By: Relevance
“…In agreement with previous reports [2,4,39] maxillary length was not significantly different between the groups. Mandibular total and body length increased from group II/1 to group II/2 by about 3 mm on average, while results from literature are conflicting [2,3,40].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In agreement with previous reports [2,4,39] maxillary length was not significantly different between the groups. Mandibular total and body length increased from group II/1 to group II/2 by about 3 mm on average, while results from literature are conflicting [2,3,40].…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, several previous studies failed to find clear differences in the basal positions between the Angle Class II subdivisions [1,2,4,28]. Some authors, however, reported a more retrognathic mandible [2,3,5,26,33,41,42] and a more obtuse ANB [3,28] in Class II division 1 as compared with division 2. Since ANB is largely affected by jaw prognathism and mandibular rotation, assessment of the anteroposterior basal relationship was additionally based upon Wits appraisal [14,43].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations